A structural equation model of relationships of health literacy, illness and medication beliefs with medication adherence among patients with chronic obstructive pulmonary disease. Issue 6 (June 2021) - Agarwal, Parul; Lin, Jenny; Muellers, Kimberly; O'Conor, Rachel; Wolf, Michael; Federman, Alex D.; Wisnivesky, Juan P.
Highlights: HL does not have direct effect on medication adherence. Medication beliefs are a partial mediator of the relationship between HL and medication adherence. Addressing medication concerns and reinforcing the need for daily COPD medications may improve adherence among COPD patients with limited HL. Abstract: Objective: To determine the relative contributions of health literacy (HL) and illness and medication beliefs to medication adherence among older COPD patients and determine the pathways through which they operate. Methods: The study was conducted using data from a prospective cohort of COPD patients in New York City and Chicago. We used structural equation modeling to examine the pathways linking HL, through medications and illness beliefs, with COPD medication adherence. Results: Out of 393 older adults with COPD, 123 (31%) had limited HL and 208 (53%) reported low adherence to daily COPD medications. Those with limited HL were more likely to have low medication adherence (p < 0.0001). Medications concerns (p = 0.001) and medication necessity (p = 0.003) demonstrated a mediational role between HL and adherence. However, in the final multivariate model, HL did not have direct effect on medication adherence (p = 0.12) and illness beliefs (p = 0.16) did not demonstrate a mediational role between HL and adherence. Conclusion: Our findings suggest that low HL is not a direct predictor of poor medication adherence among COPD patients. Practice implications: Addressing medication concerns and reinforcing the need for daily COPD medications may be a more effective strategy for increasing adherence in this population.